2021
DOI: 10.1002/onco.13794
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cancer History on Outcomes Among Hospitalized Patients with COVID-19

Abstract: Background. Early reports suggested increased mortality from COVID-19 in patients with cancer but lacked rigorous comparisons to non-cancer patients. We investigated whether a current cancer diagnosis or cancer history is an independent risk factor for death in hospitalized COVID-19 patients. Patients and Methods. We identified patients with a history of cancer admitted to 2 large hospitals between 3/13/2020 and 5/10/2020 with laboratory-confirmed COVID-19 and matched them 1:2 to patients without a history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Also, medical scientists and social scientists alike have undertaken studies from diverse perspectives both at pharmacological and non-pharmacological levels. Studies conducted at patients-level on the impact of COVID-19 by varied dimensions - such as, sex differences [ [2] , [3] , [4] , [5] ] underlying diseases [ [6] , [7] , [8] , [9] ] and physical fitness [ [10] , [11] , [12] ] - have come up with varied findings. Studies by these dimensions have contributed to further analysis and understanding of the risk factors and fatalities associated with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Also, medical scientists and social scientists alike have undertaken studies from diverse perspectives both at pharmacological and non-pharmacological levels. Studies conducted at patients-level on the impact of COVID-19 by varied dimensions - such as, sex differences [ [2] , [3] , [4] , [5] ] underlying diseases [ [6] , [7] , [8] , [9] ] and physical fitness [ [10] , [11] , [12] ] - have come up with varied findings. Studies by these dimensions have contributed to further analysis and understanding of the risk factors and fatalities associated with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we suspect that differences in inpatient versus outpatient site of care, treatment course, and disease morbidity in our NHIS sample contributed to this finding. Previous studies have described differences in clinical morbidity and outcomes of patients with blood cancers and found that patients with blood cancers were more likely to die after hospitalization with COVID-19 [ 40 , 41 ] and were more likely to die in the hospital and receive intensive care compared to patients with solid tumors [ 30 , 31 , 42 ]. Although limited in scope of analysis, these studies point to higher baseline morbidity and need for inpatient care of patients with blood cancers.…”
Section: Discussionmentioning
confidence: 99%